Effectiveness of person‐ and family‐centred care transition interventions on patient‐ oriented outcomes: A systematic review. Issue 2 (19th November 2020) - Backman, Chantal; Chartrand, Julie; Crick, Michelle; Devey Burry, Robin; Dingwall, Orvie; Shea, Beverley
Abstract: Aim: The aim was to critically analyse the body of evidence regarding the effectiveness of PFCC transition interventions on the quality of care and the experience of patients. Design: We conducted a systematic review using the Cochrane Handbook's guidelines and adhered to a standardized reporting format: Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). Methods: Four databases and grey literature were searched. Following a two‐step screening process, data from the eligible studies were extracted. Risk of bias and quality of the studies were also assessed. Narrative synthesis and vote counting were used for the data analysis. Results: A total of 28 articles met our inclusion criteria. Interventions varied in regards to the extent of the PFCC focus and the comprehensiveness of the transition of care. Educating patients to promote self‐management was the most commonly included component and it was described in all 28 interventions.